Jogos no ensino de matemática: um estudo de teses e dissertações com a perspectiva histórico-cultural - Gomes, Ana Karina Marmorato (Universidade Federal de São Carlos, 2017)
This research presents a result from the enquiry and assay of thesis about the using games when teaching math on a historical and cultural perspective. It was accomplished a list of published books at the math education field, database of thesis and essays made between 1994 and 2016, studied according to: date, academic degree, foundation, zone, school level, focus on education, topic structure and types of game. It was analyzed the main trends and found gaps, with the purpose of new studies. Most of the production was made at the Universidade Federal de São Carlos (UFSCar) and at the Universidade de São Paulo (USP). The master focus of this research it was the Elementary School. Based on topic structures and types of games, we notice that the most used it was natural numbers operations and board, computer, bowling and card games. It was also studied the possible contribution and hints of the use of games when teaching math on a historical and culture perspective at Education Basis.
Games in mathematics teaching: a study of theses and dissertations with a historical-cultural perspective
Keywords: Jogo; Perspectiva histórico-cultural; Matemática; Estado da arte da pesquisa; Game; Historical and cultural perspective; Math; State of art research; CIENCIAS HUMANAS::EDUCACAO